The issue of women's education in the Turkestan region from the 17th century to the first quarter of the 20th century - Umarova.M.Kh; Abdusamadova M.H. (Genius Journals, 2023)
This article discusses the historical evolution of women's education in the Turkestan region from the 17th century to the first quarter of the 20th century. It explores the early roots of education in the region, the influence of empires, the role of religion, and the transformative impact of Soviet educational reforms. The article highlights the challenges and progress in women's education during this period, ultimately reflecting the complex interplay of tradition, external influence, and the pursuit of women's empowerment in a historically conservative society
Keywords: Women's Education; Turkestan Region; Historical Evolution